Changing Paradigms in Indonesian Public Health Services: Disruptive Transformation Strategies - Lelyana, Nora (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
This research explores the changing paradigms in Indonesian public health services and proposes disruptive transformation strategies to address existing challenges. The background highlights inefficiencies in the current public health system, emphasizing geographical disparities, infrastructure limitations, and an inadequate healthcare workforce. The aim is to inform transformative strategies by drawing insights from international best practices, conceptualizing disruptive transformation, and identifying policy implications. Qualitative research methods using secondary data analysis were employed to investigate Indonesian public health system challenges, examine global best practices, conceptualize disruptive transformation, and analyze policy implications. The findings reveal systemic challenges, lessons from successful global models, a theoretical framework for disruptive transformation, and critical policy considerations. The conclusion emphasizes the need for a comprehensive, community-centric approach, leveraging technology and ensuring regulatory adaptability. Policy recommendations include flexible regulations, interagency collaboration, data privacy measures, equity-focused strategies, and innovative financing models. The research contributes to shaping Indonesia's resilient, inclusive public health system. Keywords: disruptive transformation, Indonesian public health, policy implications